De novo Synthesis of Modified Saxitoxins for Sodium Ion Channel Study - Andresen, Brian M. (2009)
[Image: see text] Access to novel forms of (+)-saxitoxin (STX), a potent and selective inhibitor of voltage-gated Na(+) ion channels, has been made possible through de novo synthesis. Saxitoxin is believed to lodge in the outer mouth of the channel pore, thereby stoppering ion flux. Herein, we demonstrate that modification of the C13-carbamoyl unit can be accommodated in the binding site of the protein without significantly reducing ligand-receptor affinity. These discoveries have emboldened efforts to prepare photoaffinity-labeled and other unique forms of STX as pharmacological tools for interrogating both the molecular architecture and function of Na(+) channels. A synthetic plan is described that makes such compounds generally available.